Pengaruh Pendidikan Formal Orangtua terhadap Perkembangan Sosial Emosional Anak di Madrasah Ibtidaiyah Thoriqus Salam Sidoarjo - Hakim, Abd (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2020)
Elementary School education is a coaching effort undertaken for 6-year-old children carried out with the help of educational stimuli to support physical and spiritual growth and development so that children have readiness in education to continue. Efforts given to early childhood are in the form of stimulating, guiding and nurturing and providing learning activities that will produce children's abilities and skills that are adapted to the child's development in the past. This is based on Law No. 20 of 2003 concerning the national education system Chapter 1, Article 1, Item 14. In accordance with the research questions that have been raised, the purpose of the study is to find out the parents' formal education towards the social development of children in Madrasah Ibtidaiyah Thoriqussalam Sidoarjo. There is a significant influence between formal education on children's emotional social development in RA Madrasah Ibtidaiyah Thoriqussalam Sidoarjo. Two independent variables namely formal education are correlated, with different significance ,. The higher the formal education the better the higher the social development of children or vice versa which is being discussed with the regression analysis that occurs. Based on the research conclusions, the authors can propose the following suggestions: (1) Early Childhood Education teachers can consider that there are dominant factors regarding formal education that can facilitate children's emotional social development in addition to other factors (2) Adjusting patterns the mindset or perspective between teachers and students, intensive communication is improved between teachers and funds. In bringing this mindset together, teachers and parents must sit together, discuss what education can be done at home and what education should be done at school.